2017
DOI: 10.1007/s10107-017-1153-4
|View full text |Cite
|
Sign up to set email alerts
|

Minimal cut-generating functions are nearly extreme

Abstract: We study continuous (strongly) minimal cut generating functions for the model where all variables are integer. We consider both the original Gomory-Johnson setting as well as a recent extension by Cornuéjols and Yıldız. We show that for any continuous minimal or strongly minimal cut generating function, there exists an extreme cut generating function that approximates the (strongly) minimal function as closely as desired. In other words, the extreme functions are "dense" in the set of continuous (strongly) min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In our opinion, this result alone is likely to be a very useful tool for subsequent research in the area. Similar non-trivial departures from the techniques of [7] are required to obtain our main result.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…In our opinion, this result alone is likely to be a very useful tool for subsequent research in the area. Similar non-trivial departures from the techniques of [7] are required to obtain our main result.…”
Section: Introductionmentioning
confidence: 77%
“…In [7], Basu, Hildebrand, and Molinaro observed a curious property for the convex set of continuous minimal functions π : R → R, i.e., with n = 1. Moreover, they demonstrated that the extreme points of this convex set are dense in this set (under the topology of pointwise convergence).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations